KESULITAN GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI BERDASARKAN KURIKULUM 2013 DI SMP NEGERI 6 KOTA MAKASSAR - Umar Umar (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
This research aimed at describing the teachers’ difficulties in teaching Islamic education and character based on curriculum 2013 at SMPN 6 Makassar. This Research used qualitative by using phenomenologis8t approach. The data were obtained from the teachers of Islamic education, the head master, and the vice head master of curriculum concerns, advisor and students. Data were collected from observation, interview, documentation tools, triangulation, and literature review. Then the data were analyzed by using Miles’ and Huberman’s model analysis through four steps namely; data reduction, data presentation, drawing conclusion and data validation. The research finding shows that in conducting learning process based on curriculum 2013, teachers encountered some difficul-ties in teaching such as; they find difficulty to choose the suitable instructional model related to scientific approach, they encountered difficulties in making instruments and evaluation formats, and they also faced difficulties in the process of evaluation. But, generally, they encountered more difficulties in using authentic assessment of the curriculum 2013.